Data Transfer Schemes in Rotorcraft Fluid-Structure Interaction Predictions - Young H. You; Deokhwan Na; Sung N. Jung (International Journal of Aerospace Engineering, 2018)
For a CFD (computation fluid dynamics)/CSD (computational structural dynamics) coupling, appropriate data exchange strategy is required for the successful operation of the coupling computation, due to fundamental differences between CFD and CSD analyses. This study aims at evaluating various data transfer schemes of a loose CFD/CSD coupling algorithm to validate the higher harmonic control aeroacoustic rotor test (HART) data in descending flight. Three different data transfer methods in relation to the time domain airloads are considered. The first (method 1) uses random data selection matched with the timewise resolution of the CSD analysis whereas the last (method 2) adopts a harmonic filter to the original signals in CFD and CSD analyses. The second (method 3) is a mixture of the two methods. All methods lead to convergent solutions after a few cycles of coupling iterations are marched. The final converged solutions for each of the data transfer methods are correlated with the measured HART data. It is found that both method 1 and method 2 exhibit nearly identical results on airloads and blade motions leading to excellent correlations with the measured data while the agreement is less satisfactory with method 3. The reason of the discrepancy is identified and discussed illustrating CFD-/CSD-coupled aeromechanics predictions.